Hubungan Antara Pola Asuh Orang Tua Dan Perilaku Tantrum Pada Anak - Anjarwati, Titis; Widya Novita Sari; Hidayatu Munawarah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This article aims to find out how the parenting style taught by parents is related to students' behavior when entering education, namely elementary school, especially grade 1, where tantrums often occur in the school environment. In this case, children not only need genuine assistance from school teachings, but also from their parents' parenting style. This reflection of parents in educating is what children express when they enter their social environment, namely the school environment. Cases of children who have problems or tantrums in the school environment are closely related to what parents teach their children. The research method we use in this writing is qualitative with case study techniques, namely several data collection methods including interviews and observation. The results of this research are that teachers as facilitators cannot 100% supervise and calm children when they have tantrums in the school environment. This is caused by parents often pampering them, being supervised during learning activities, and not giving children the opportunity to interact with their environment and friends, which makes children not socialize.